Scrutinizing Crop production from Ayamaru Timur District, Maybrat-Southwest Papua Province; Land-Use and Agribusiness Cycles’ Potential - Sagrim, Meky; Iyai, Deny Anjelus (Jurnal Dinamika Sosial Ekonomi, 2025)
Understanding the land-use potential in Ayamaru Timur District, Maybrat-Southwest Papua Province provides insights into optimizing agricultural activities to boost local economies and ensure sustainable development in the region. The aims of study are to explore the land-use potential and agribusiness cycles in Ayamaru Timur District by analysing physiographic characteristics, soil types, and existing land utilization patterns, the research identifies opportunities and challenges for optimizing agricultural productivity. Methods employed are field observation in on land-uses of farming land and surveys by interviewing key farmers using open structural questionnaire. Samples of soils then analysed in the Soil Laboratory of Agriculture Faculty, Papua University for further syntheses.  Parameters measured are physiographic of lands, soil types and suitability, crop types and actual and potential suitability, types of crops including production and productivities, revenue, cost and added to this income generation. Major challenges are recorded for future policy development. Data presented by statistical descriptives and tabulations. The finding revealed that land suitable ranges from marginal to moderately suitable. Potential land-uses are agroforestry crops, food crops, and plantation crops. Non-agricultural land (1%), followed by agroforestry crops, food and plantation crops are actually useable by farmers. Crops grown are tubers, vegetables, non-tuber crops and legumes. Revenues earned firstly from vegetables (IDR 1,890,476), followed by tuber crops (IDR 926,506), Nuts (IDR 486,170), and non-tubers (IDR 420,000). In conclusion, vegetables, tuber and non-tuber crops, including legumes have potential for agricultural development.